Science and technology education network - De La Salle University, Manila (Animo Repository, 1996)
EVP Dr. Carmelita Quebengco signed a Memorandum of Agreement with the Department of Science and Technology to develop a Philippine database in Science Education known as Science and Technology Education Network (STEDNET) as a centralized source of material and information in science and education. Dr. Ester Ogena, Director of Science Education Institute, signed for DOST.